Manure management in the (sub-)tropics; Training manual for extension workers - Teenstra, E.; Buisonjé, F. de; Ndambi, A.; Pelster, David E. (Wageningen University & Research, 2015)
Having identified a general lack of knowledge about the value of livestock manure and integrated manure management at multiple levels in government and society, a concerted action led to the compilation of a training manual for extension workers on manure management in the (sub-)tropics. Covering the whole manure chain, from animal excretion to the final application, the manual describes the basic principles of integrated manure management. Although much information originates from more temperate regions, the manual focusses on farm practices in the tropics and subtropics.